+0  
 
0
42
1
avatar+319 

What are the solutions to the equation?

SamJones  Jan 17, 2018
Sort: 

1+0 Answers

 #1
avatar+82937 
+1

x^2 ( 4x - 3)  (5x - 1)  =  0

 

Set each factor to 0 and solve

 

x^2   = 0     ⇒  x  = 0

 

4x - 3  =  0     add 3 to both sides

4x  = 3           divide both sides by 4

x  =  3/4

 

5x - 1  = 0      add 1 to both sides

5x  =  1     divide both sides by  5

x  =  1/5

 

 

cool cool cool

CPhill  Jan 17, 2018

9 Online Users

We use cookies to personalise content and ads, to provide social media features and to analyse our traffic. We also share information about your use of our site with our social media, advertising and analytics partners.  See details